Proceedings of the 2013 Conference on Computer Supported Cooperative Work 2013
DOI: 10.1145/2441776.2441920
|View full text |Cite
|
Sign up to set email alerts
|

Crowd vs. crowd

Abstract: Following the recent remarkable successes of crowdsourcing, there have been attempts to apply it to design. However a design problem is often too complex and difficult to break down into simpler, distributable tasks as required by the conventional crowdsourcing model. In this paper, we present Crowd vs. Crowd (CvC), a novel design crowdsourcing method, where several design teams made up of designers and crowd compete with each other. In each team, a designer coordinates effective communication between the crow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Their study showed that their system resulted in better performance over pre-authored tutorials by improving learner performance, increasing motivation, and stimulating knowledge transfer. Park et al [34] presented a novel crowdsourcing method, where several design teams made up of designers and crowd compete with each other. They observed that the elements of competition and collaboration helped to sustain the crowd's motivation to participate, and that quality design outcomes were produced with a higher level of satisfaction for the stakeholders.…”
Section: Social Incentivesmentioning
confidence: 99%
“…Their study showed that their system resulted in better performance over pre-authored tutorials by improving learner performance, increasing motivation, and stimulating knowledge transfer. Park et al [34] presented a novel crowdsourcing method, where several design teams made up of designers and crowd compete with each other. They observed that the elements of competition and collaboration helped to sustain the crowd's motivation to participate, and that quality design outcomes were produced with a higher level of satisfaction for the stakeholders.…”
Section: Social Incentivesmentioning
confidence: 99%
“…Crowd vs. Crowd (CvC) [31] used competitions between crowd teams, led by a designer, to crowdsource the entire design process. One limitation of these systems was that they focused on asynchronous interactions and highly structured, iterative, tasks.…”
Section: Crowdsourcing In the Design Processmentioning
confidence: 99%
“…Readers are referred to Park et al. (2013) and Schmidt (2017) for a review of recent development of various crowdsourcing implementations in the corresponding industries.…”
Section: Introductionmentioning
confidence: 99%
“…These applications share a similar business principle where a firm or an individual fulfills his/her needs (for either goods or services) by tapping into a large and diverse crowd of potential contributors. Readers are referred to Park et al (2013) and Schmidt (2017) for a review of recent development of various crowdsourcing implementations in the corresponding industries.…”
Section: Introductionmentioning
confidence: 99%